Retooling Coconut Peeling Machine for Community Empowerment in Paloh Punti Village Muara Satu - Putra, Reza; Muhammad, M; Asnawi, A; Islami, Nurul; Sayuti, Muhammad; Murdani, Murdani; Wahyuni, Rita (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
The partner in this PKM is Paloh Punti Village, Muara Satu, Lhokseumawe City. Paloh Punti Village is one of the villages in the Unimal Campus area which is 3 km from the Bukit Indah Campus. In general, the jobs of the people in Paloh Punti village are farmers and livestock breeders. Almost 80% of plantation land in this village is planted with coconut trees. Selling coconut plantation products is one of the main sources of income for the people of Paloh Punti village. So far, the selling value of coconuts in the Paloh Punti area is relatively low, ranging from 1,800 to 2,000 rupiah. This low selling value is due to the coconut plantation owners selling their produce intact, known in the community as round coconuts. To increase the selling value of these coconuts, the Community Service is trying to offer assistance in making a Coconut Skin Peeling Machine which will later be donated to the Paloh Punti Village Community under the coordination of the Village Leadership. This service will be carried out in stages, starting with counseling, introduction to peeling tools/machines, testing the tools, evaluating the economic value and handing over the coconut peeling machine to the village leadership. Counseling and training on the use of this tool begins with designing a tool using the ATM method (Observe, Imitate and Modify) from pre-existing types of equipment and adapt it to the needs of supporting machines.